”En lugn och karlfri hamn”: Kvinnorna och hemmet i Elin Wägners Pennskaftet - Pärsson, Sara (Tidskrift för litteraturvetenskap, 2020)
”A Peaceful, Male-free Refuge”: Women and their Homes in Pennskaftet by Elin Wägner This article explores how homes and ideas about a woman’s place are depicted in the Elin Wägner novel Pennskaftet (1910). In the novel, social and spatial roles of women are depicted and discussed as full of political andexistential meaning. Sara Ahmed’s Queer Phenomenology (2006) provides concepts for the analysis. The concepts orientation, the straight line, and Ahmed’s thoughts on the process of inhabiting are used to explore how the New Women of the novel choose to live and what values they ascribe to the home. Throughout the novel there is a longing for a home of one’s own. By focusing on the wishes and needs of women, the novel states that the home is a woman’s place: a place to rest, think, write, grieve – maybe even a place of marital bliss.